Incidence and Fate of Acute Kidney Injury in Patients Admitted to Pediatric Intensive Care unit - ali, ashwaq (Karbala Journal of Medicine, 2021)
Introduction: Acute Kidney Injury (AKI) is a clinical condition that commonly occurs in critically ill patients in the pediatric intensive care unit (PICU) with mortality rate of between (30-44)%. Objectives: The aim of this study was to determine the incidence and stages of AKI and the short-term clinical outcome in patients admitted to PICU of Babylon Teaching Hospital for Gynecology and Children. Methods: This observational study involved 156 patients aging more than one month admitted to pediatric intensive care unit (PICU) of Babylon teaching hospital for gynecology and children over 1 year. For each patient, renal functions were assessed: measurement of serum creatinine and blood urea at time of admission then repeated every 24hrs whenever indicated. Monitoring of amount of urine output every hour. We used classification system proposed by the Kidney Disease Improving Global outcomes (KDIGO) to define acute kidney injury stages Results: Acute kidney injury occur in 45 patients (31%) of study group while 98 patients (69%) were free from kidney injury. Majority 27 patients (60%)) of total patient with Acute renal injury presented with stage 1, 10 patients (22%) presented with Stage 2 and 8 patients (18%) presented with stage 3. Patients with AKI showed higher mortality (33.3) % compared with (22.4) % from patients without AKI. Conclusion: AKI in critically ill children is found to have a high incidence and higher mortality,